Impact of recent changes in protocol on the management of anaemia in pregnancy in NHS Tayside: a retrospective audit. (18th April 2012) - Graham, N; Bandyopadhyay, S; Lynch, P
Abstract : Background: Anaemia is the most common medical condition in pregnancy. To tackle the problem of anaemia and reduce the rate of blood transfusion in NHS Tayside, the following key changes were implemented recently - A routine Hb check at 28 weeks and more aggressive treatment with oral and intravenous iron preparation. Aims and Objectives: To assess the prevalence of anaemia, efficacy of our current management and to compare the current management with the last audit Methods: Data collected retrospectively from 'Central Vision' software system about blood results of all women delivered in Tayside for 2 weeks in Feb 2011. We, then, studied the patients' case notes. Results: 152 women had delivered during this time period, out of which only 23% had Hb of <11gm% at 28 weeks (compared to 35.6% in 2006). Though 10 mothers had significant PPH (>1000 mls), only 2 of them had blood transfusion. We also compared the rate of blood transfusions in 2006 and 2010. The number of packed red cells has decreased from 225 to 179 even when the rate of delivery and pregnancy complications has increased. The rate of FFP usage has gone up significantly. Conclusion: This audit clearly shows that anaemia is managed more efficiently and aggressively now than in 2006. Our blood transfusion rate has decreased despite changes in demographics and the incidence of PPH is on the rise. Introduction of routine Hb testing at 28 weeks and judicious use of intravenous iron therapy has allowed us to treat anaemia more effectively.